PEMANFAATAN KOTORAN SAPI MENJADI PUPUK ORGANIK (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
Lack of knowledge of both the theoretical and practical issues of benefits, functionality and how to make organic fertilizer to make the most of the villagers Imaan, Gresik use chemical fertilizers or inorganic fertilizers as the main material to increase their agricultural output. Society/ farmers do not quite understand that the long term use of inorganic fertilizers will erode nutrients and other essential minerals in the soil causing the soil becomes less fertile and ultimately it will impact on the lack of yield even crop failure. Based on the above data that the author can be through direct observation and interviews with villagers Imaan, the writer took the initiative to conduct counseling and training on how to make organic fertilizer from cow manure by using the main ingredient EM-4 plus other materials that exist around citizen. Selection of cow manure as an alternative to organic fertilizer is because the average citizen to keep cow as cattle, besides it has been resident who use manure as fertilizer. The result of citizens then began to realize the benefits of organic fertilizers as well as the danger of an organic fertilizer. Residents also came to realize that the use of organic \ertilizers is more cost-effective and are keen to start using cow manure and other animal waste in general as a soil conditioner media replace inorganic fertilizer.